The effect of selected exercise training on reduce symptom of hypotonia and changing body composition in men with Down syndrome - Ali Kashi; Manhood Sheikh; Asghar Dadkhah; Rasool Hemayattalab; Elahe Arabameri (University of Tehran, 2015)
The aim of this research was to determine the effect of selective exercise training on reducing the symptom of hypotonia and changing body composition in Down syndrome adults. The research was performed in Nemoneh Disability Rehabilitation Centre of Tehran. 24 men with Down syndrome (mean age 26.185± 3.933) were randomly assigned to either a control (n=11) or an experimental group (n=13). The Experimental groups followed selective exercise training for 12-weeks, three times a week. Result of this research showed that after 12 weeks selective exercise training, body fat percent had a significant reduction (P<0.05) and soft lean mass and muscle performance (in 5 from 6 tests for assess muscle strength, endurance and power) had a significant increase (P<0.05). The results of this study showed that this type of exercise training significantly improves the health of Down syndrome adults by reduce in extra body fat percent and increase in muscles tissue and performance and in this way; it will reduce the symptoms of Down syndrome for benefit of improved physical health.